Penggunaan emotional appeals pada niat berdonasi (guilt appeals vs sadness appeals): sudut pandang Theory of Planned Behavior - Zuyyinna Choirunnisa; Tanti Hendriyana; Sri Hartini (Jurnal Ekonomi Modernisasi, 2019)
The objective of this study is to compare the use of emotional appeal (guilt appeals and sadness appeals) on donation advertisement on Rohingya social disasters against the intention of donating using the perspective of Planned Behavior Theory. The research method used in this research is quantitative research with experimental design with convenience sampling, that is, master sudent at Airlangga University. By using ANOVA test and multiple linear regression, this study answers the hypothesists. The results show that sadness appeals has greater impact than guilt appeal in the formation of subjective norms and perceived behavioral control. In addition, this study found that behavioral control not signifiacantly impact the intention of donating. This research also provides implications for nonprofit organizational managers to pay attention in delivering information of donation to donors, because respondents had begun to more sensitive of the type of advertising framing.